Analisis strategi pemasaran produk dendeng ikan di UMKM Belia Jaya Kabupaten Aceh Besar - Ulfa, Fitria; Zuraidah, Syarifah; Akbardianysah (Jurnal Sosial Ekonomi Perikanan, 2023)
Belia Jaya is an MSMEs engaged in processing in the form of products fisheries, one of which is beef jerky with goats. This study aims to find out what marketing strategies are appropriate and appropriate in marketing goat and goat jerky products. The location of this research was conducted at MSMEs Belia Jaya kec. Kuta baro Aceh Besar District, with a total of 5 respondents consisting of 1 leader and 4 employees at MSMEs Belia Jaya. The analysis used is SWOT analysis. The results of the study show that the condition of the Belia Jaya MSMEs is in the first quadrant. This shows that the Belia Jaya MSMEs is in a very favorable condition because it has quite good strengths and opportunities. Swot matrix analysis shows alternative strategies that can be applied by MSMEs Belia Jaya, namely: (1) Utilizing cooperative relations and government support; (2) Expanding the marketing network; (3) Increasing production volume with a variety of packaging; (4) Optimizing the use of technology and information to increase market access; (5) Improving product quality and quality in order to compete; (6) Maintain existing quality at an affordable price; (7) Carrying out product development through new innovations in order to compete with new competitors.